Servant leadership from the Muslim perspective - Ahmad , Khaliq; Abdul Kadir, Mohd Ali Bahari (Malaysian Institute of Management, 2012)
This paper has been prepared to discuss contemporary issues in leadership, and also serves as a means of reviewing the literature in the area of Servant Leadership. Islamic leadership principles and a spiritual dimension in leadership are touched upon. The main purpose of this paper is to better understand the aforesaid leadership terms through empirical data, since most Islamic leadership theories are hardly supported by on the ground facts and realities.